ASUHAN KEPERAWATAN ANAK THALASEMIA PERBANDINGAN PENGKAJIAN EMERGENCY NEUROLOGI MENGGUNAKAN SIRIRAJ SCORE (SS) DENGAN METODE NATIONAL INSTITUTE OF HEATH STROKE SCALE (NIHSS)PADA PASIEN STROKE DI RUMAH SAKIT ISLAM JOMBANG - Saudin, Didik; Pramono, Pramono (Universitas Pesantren Tinggi Darul Ulum, 2018)
Stroke cases in Indonesia have increased every year in East Java, the number of stroke cases has increased by 16%. The success of handling stroke depends on the speed, accuracy and accuracy of the beginning of the incident. Based on existing stroke cases, a comprehensive assessment method is needed, it aims to determine the appropriate action in stroke patients so as to minimize the severity of the stroke. The National Institutes of Health Stroke Scale (NIHSS) study is the first step in the nursing process by collecting accurate data to minimize the level of disability and death in stroke cases. Using statistical analysis between assessors, reliability was determined by calculating the intraclass correlation coefficient (ICC) using the ANOVA test. Retrospectives represent clinically relevant values. Receiver operator characteristics (ROC) were used as an accuracy of NIHSS assessments. Clinically or statistically significant differences between estimated mean scores correspond to 6 assessors (ANOVA: overall P = 0.15, entry P = 0.28, discharge P = 0.59). The pair of assessors were also very good at ICCs ranging from 0.70 to 0.89. a partner of more than 90%. The estimated value of NIHSS is 5 points with a high level of reliability and validity. NIHSS is designed as a tool to measure stroke patients. this scale to evaluate the sharpness of stroke patients, determine the right treatment, and predict the outcome of stroke patients.Keywords: NIHSS, Stroke Specifications